Contemporary Issues and the rulings on women’s veiling in the light of shsria - Asia Bakht Pari; Associate Professor Dr. Naseem Akhter (Journal of Religion and Society, 2025)
In Islamic teachings veiling hijab is a fundamental religious commandment aimed at maintaining modesty and social purity.scholarly discussions on this topics, titled the rules and issues of the of the veil in the modern era, emphasize the following the difference between the seven hijabs, veils, jilbabs, khimar and niqab, the book clarifies the legal and literal differences between these different terms so that the scope of each can be understood. Arguments have been given on the necessity, importance, and vvidom of the veil, the religious status of the veil, and its social benefits, including the propection of women and the formation of an Islamic society. The veil and the demands of the modern era: The issues were examined. Whether the veil is an obstacle to women’s education and development or not.from an Islamic perspective, the veil is not an obstacle to development, but rather it is part of the identity and dignity of a Muslim women. Practical issues: Detailed guidance is provided on important and everyday issues such as the shariah status of adopting current fashions such as the black abaya and the injunctions to cover oneself from non-mahram relatives. The veil for Men is not only for women in Islam .The injunctions regarding men’s veil, lowering their gaze, and maintaining modesty were also discussed. Keywords: Women’s Veiling (Hijab), Contemporary Challenges, Islamic Jurisprudence (Fiqh), Shariah Rulings, Modesty and Gender Ethics